Isolation, Screening, Characterization, and Identification of Potential Probiotic Lactic Acid Bacteria (LAB) from the Gut of Whiteleg Shrimp (Litopenaeus vannamei) - Nguyen Phuong, Thuy; Nguyen Thanh, Tuu (Bogor Agricultural University, Indonesia, 2026)
Bacterial diseases represent a major constraint on the sustainability of shrimp aquaculture. Increasing antibiotic resistance necessitates eco-friendly alternatives. This study isolate and characterizes bacteriocin-producing Lactic Acid Bacteria (LAB) from the gut of healthy farmed Litopenaeus vannamei to evaluate their probiotic potential. Thirty presumptive LAB isolates were obtained from 50 shrimp samples. In vitro assessment included tolerance to simulated gastrointestinal conditions (pH 1.5 and 3% bile salts), safety (hemolysis and antibiotic susceptibility), and antimicrobial activity against four pathogens: Vibrio parahaemolyticus, V. harveyi, V. alginolyticus, and V. vulnificus. Isolate LV4 maintained viable counts of 6.72±0.13 Log CFU/mL at pH 1.5 and 5.17±0.48 Log CFU/mL at 3% bile salts. The neutralized cell-free supernatant of LV4 exhibited proteinaceous, broad-spectrum antimicrobial activity against all tested Vibrio pathogens. Isolate LV4 was non-hemolytic and sensitive to most clinically relevant antibiotics. Molecular identification using 16S rRNA gene sequencing identified LV4 as Enterococcus faecalis. This study confirms that the gut of L. vannamei is a valuable reservoir for robust LAB. Isolate E. faecalis LV4 is a strong candidate for further development as a probiotic to enhance shrimp health and disease resistance in aquaculture.